PENENTUAN KADAR BESI (Fe) AIR SUMUR DAN AIR PDAM DENGAN METODE SPEKTROFOTOMETRI - KHAIRA, KUNTUM (Sainstek : Jurnal Sains dan Teknologi, 2013)
The purpose of  research is determine of molecule of Fe2+ from well and PDAM. This research used two sample, they are from well and PDAM. This research used spectrophotomery using 1.10 phenantroline solution. Phenantroline would change all ferrous ion to Fe2+ dissoluable. Three molecules of phenantroline joint with one molecule of Fe2+  form orange-red complex ion. Reffering to Standarization from Healthy Minister of Republic Indonesia No. 492/MENKES/PER/IV/2010, the allowable maximum ferrum concentration in the drinking water is 0,3 ppm. The experiment showed that the ferrum concentration of well were 0,08 and 0,054 g/mL and the ferrum concentration of PDAM were 0,636 mg/L, 2,004 mg/L, 1,939 mg/L, 0,226 mg/L, 0,627 mg/L and 1,003 mg/L.Key words: drinking water,  molecule of Fe2+, spectrophotomery